Comparison between Resistograph Analysis with Physical Properties of the Wood of Brazilian Native Tree Species - Silva,Carlos Eduardo Silveira da (2020)
ABSTRACT There is just little information about the technological aspects of the wood of Brazilian native tree species, which limits their suitable use. The objective of this study was to evaluate the resistograph amplitudes of the wood from six native tree species in different wood density classes, and correlate them with their wood densities to demonstrate the efficiency of this nondestructive technique. The results of the resistograph analysis divided the species into three classes. Analyses of basic and bulk densities of their wood showed statistically significant differences among the evaluated samples that divided them into four classes. The comparison of resistograph method and observed densities showed only a slight difference among the density classes. Therefore, it was found in this study that resistograph analysis may be used for explaining wood properties as well as achieving satisfactory correlations with their actual values, especially the physical properties of species with high wood density.